57.2k views
1 vote
Consider the expression below.

(x-1)(x-7)

For (x - 1)(x - 7) to equal 0, either (x - 1) or (x - 7) must equal
.

The values of x that would result in the given expression being equal to 0, in order from least to greatest, are
and
.

User Ivvi
by
5.8k points

2 Answers

2 votes
(x-1) = 0 or (x - 7) = 0
x = 1 or x = 7

Answer: 1, 7
User Miladfm
by
5.4k points
4 votes

Answer:

The values of x that would result in the given expression being equal to 0, in order from least to greatest, are 1 and 7

Explanation:


(x-1)(x-7)

WE need to find the value of x that make the expression 0

we set the given expression =0 and solve for x


(x-1)(x-7)=0

Set each factor =0 and solve for x

x-1=0 (add 1 on both sides)

x=1

x-7=0 (add 7 on both sides)

x=7

The values of x that would result in the given expression being equal to 0, in order from least to greatest, are 1 and 7

User Jeff Posnick
by
5.3k points